!<Answer>!
Directions: Write each exponential equation in logarithmic form.
1. 26 = 64
The exponential form is: base^exponent = result
So, in logarithmic form, it becomes: log base(result) = exponent
Therefore, the logarithmic form of 26 = 64 is: log base 2 (64) = 6
2. 4-2-¹ = 1/16
The exponential form is: base^exponent = result
So, in logarithmic form, it becomes: log base(result) = exponent
Therefore, the logarithmic form of 4-2-¹ = 1/16 is: log base 4 (1/16) = -2
3. 0 - 12/17 = -12/17
There seems to be an error in the question. The given expression is not an exponential equation, so it cannot be written in logarithmic form. Please double-check the question.
4. 37 = 2187
The exponential form is: base^exponent = result
So, in logarithmic form, it becomes: log base(result) = exponent
Therefore, the logarithmic form of 37 = 2187 is: log base 3 (2187) = 7
5. 12² = 144
The exponential form is: base^exponent = result
So, in logarithmic form, it becomes: log base(result) = exponent
Therefore, the logarithmic form of 12² = 144 is: log base 12 (144) = 2
Write each logarithmic equation in exponential form.
6. 5³ = 125
The logarithmic form is: log base(result) = exponent
So, in exponential form, it becomes: base^exponent = result
Therefore, the exponential form of log base 5 (125) = 3 is: 5³ = 125
Please note that for question 3, there seems to be an error in the given expression, as it does not match the format of an exponential equation.
Sun <3